Golgi Phosphoprotein 3 Mediates Radiation-Induced Bystander Effect via ERK/EGR1/TNF-α Signal Axis - Feng Qin; Guodong Chen; Kwan Ngok Yu; Miaomiao Yang; Wei Cao; Peizhong Kong; Shengjie Peng; Mingyu Sun; Lili Nie; Wei Han (MDPI AG, 2022)
The radiation-induced bystander effect (RIBE), an important non-targeted effect of radiation, has been proposed to be associated with irradiation-caused secondary cancers and reproductive damage beyond the irradiation-treated area after radiotherapy. However, the mechanisms for RIBE signal(s) regulation and transduction are not well understood. In the present work, we found that a Golgi protein, GOLPH3, was involved in RIBE transduction. Knocking down GOLPH3 in irradiated cells blocked the generation of the RIBE, whereas re-expression of GOLPH3 in knockdown cells rescued the RIBE. Furthermore, TNF-α was identified as an important intercellular signal molecule in the GOLPH3-mediated RIBE. A novel signal axis, GOLPH3/ERK/EGR1, was discovered to modulate the transcription of TNF-α and determine the level of released TNF-α. Our findings provide new insights into the molecular mechanism of the RIBE and a potential target for RIBE modulation.